Antibiogram and antibacterial activity of Crassocephalum crepidioides (Thickhead) leaf extract against the wound isolates - Yumnam Asha Devi, Prathiba Gnanasekaran, Haorongbam Joldy Devi , Durairaj Siva, Srividya Seshadri, Malathy Balaraman Ravindrran, Subashini Partheeban, Bhuvaneswari S. (Journal of Applied Pharmaceutical Science, 2025)
This study aims to evaluate the antibiogram and antibacterial activity of Crassocephalum crepidioides leaf extract against the bacterial strains isolated from infected wounds. A total of 69 swab samples were obtained from various cases of infected wounds and 20 pure bacterial strains were isolated. The most prevalent organisms isolated from wound infections were Staphylococcus species and Escherichia coli (25%), followed by Klebsiella species (15%), Proteus species (10%), Providencia species (10%), Pseudomonas aeruginosa (5%), Acinetobacter baumannii (5%), and Enterobacter hormaechei (5%). The susceptibility pattern of all bacterial isolates was assessed against antibiotic discs using the Kirby Bauer Disc diffusion method. The results revealed that Gram-positive cocci exhibited 100 % susceptibility to Amikacin, Bacitracin, Oxytetracycline, and Vancomycin, however, showed 80% resistance to Novobiocin, Amoxicillin, Cephalothin, Erythromycin. Conversely, Gram-negative bacilli exhibited high resistance levels, including 86.7% to Ciprofloxacin, 80% to Carbericillin and Nitrofurantoin, 66.7% to Streptomycin and Tetracycline, 60% resistance to Co- Trimazine; however, they showed 73.3% sensitivity to Amikacin and 53.3% sensitivity to Kanamycin. Among the 20 bacterial strains, 13 (65%) were identified as multidrug-resistant (MDR) and 4 (20%) were extensively drug-resistant (XDR). In vitro antibacterial activity assay revealed that C. crepidioides leaf extract was found to be effective against all the Staphylococcus spp., E. hormaechei, A. baumannii, Providencia spp., two E. coli isolates and one Klebsiella spp. with the zone size ranging from 10.83 ± 0.28 to 25.83 ± 1.04, with minimum inhibitory concentration between 2.5 and 40 mg/ml, however, resistant to P. aeruginosa, Proteus spp., three E. coli isolates and two Klebsiella spp. Staphylococcus spp. was found to be the most inhibited wound isolates by C. crepidioides leaf extract. These findings suggest that C. crepidioides leaf extract has the potential to develop antibacterial agents against the MDR and XDR organisms causing wound infection, emphasizing the significant role of plant extracts in treating bacterial wound infections, thereby preventing the delay of the wound healing process.
Keywords: Wound infection, bacterial isolates, antibiotic sensitivity, Crassocephalum crepidioides leaf extract, antibacterial activity